Rancang Bangun Sistem Informasi Manajemen Pasien Rawat Jalan pada Rumah Sakit Umum Daerah Waikabubak - Delviana Daijo Malli; Adelbertus Umbu Jangga; Diana Reby Sabawaly (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
The purpose of developing an outpatient management information system at Waikabubak Regional Hospital is to improve the efficacy and efficiency of the outpatient health service process. The system created will facilitate recording, managing, and monitoring patient health status in real-time. Current manual procedures often result in inaccurate recording, slow administration, and substandard medical data management. This information system is expected to facilitate medical decision-making and smooth the flow of information from patient registration and health checks to treatment and follow-up.